2019
DOI: 10.1007/s10508-019-01470-7
|View full text |Cite
|
Sign up to set email alerts
|

Syndemics and the PrEP Cascade: Results from a Sample of Young Latino Men Who Have Sex with Men

Abstract: Young Latino men who have sex with men (MSM) are a highly vulnerable population for HIV infection. Pre-exposure prophylaxis (PrEP) is a novel biomedical HIV prevention tool that may aid in reducing the disparity in HIV incidence among Latino MSM. However, PrEP use is disproportionally low among Latino MSM and, therefore, identifying barriers along the PrEP continuum of care (the "PrEP cascade") would provide insight into how to best deploy PrEP interventions. Syndemics theory is a prominent framework employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 50 publications
1
79
0
Order By: Relevance
“…We found no differences in PrEP use for Black and Hispanic/Latino MSM compared with White MSM, similar to other recent studies 8,44,54,55 but in contrast with earlier research. 10,[16][17][18] This could be due to biases in our sample, which was recruited from urban areas and highly educated, similar to studies that found no significant racial/ethnic differences in PrEP use when controlled for urbanicity and education levels. 8,44 However, given that MSM of color have higher HIV incidence than White MSM, equivalent levels of PrEP use might still not translate to equitable prevention and widen disparities in HIV incidence.…”
Section: Use Of Prep Currently Previously and Neversupporting
confidence: 55%
See 2 more Smart Citations
“…We found no differences in PrEP use for Black and Hispanic/Latino MSM compared with White MSM, similar to other recent studies 8,44,54,55 but in contrast with earlier research. 10,[16][17][18] This could be due to biases in our sample, which was recruited from urban areas and highly educated, similar to studies that found no significant racial/ethnic differences in PrEP use when controlled for urbanicity and education levels. 8,44 However, given that MSM of color have higher HIV incidence than White MSM, equivalent levels of PrEP use might still not translate to equitable prevention and widen disparities in HIV incidence.…”
Section: Use Of Prep Currently Previously and Neversupporting
confidence: 55%
“…[11][12][13] PrEP use and persistence are lower for MSM who are younger (18-24 years), of racial/ethnic minorities, and living in the US South. 8,10,11,[13][14][15][16][17][18][19][20][21][22][23][24] Prior research found that condomless anal sex (CAS), substance use, lack of insurance, and other sociodemographic factors were associated with current PrEP nonuse. 8,19,[25][26][27] Research on PrEP discontinuation is increasing; associated factors are younger age, substance use, fewer sex partners, being single, and lack of insurance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A future direction of study is the measurement of structural syndemic conditions (e.g. housing instability, criminal justice involvement, poverty [43,79]) to understand how structural barriers influence individual transmission risk. Measurement of structural syndemic conditions would bolster a case for testing interaction effects among the syndemic conditions to enable an understanding of how variables at multiple levels exacerbate HIV health outcomes [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these articles focused on characterizing the PrEP cascade, several articles aimed to examine predictors of certain steps in the PrEP cascade. Blashill et al (2019) explored the association between syndemics (i.e., multiple co-occurring epidemics related to HIV risk) and the PrEP cascade among young Latino gay and bisexual men in southern California. This study found that as the number of self-reported syndemic indicators increased (e.g., depression, substance use), the odds of engagement in all steps of the PrEP cascade decreased.…”
mentioning
confidence: 99%